Delayed administration of dopaminergic drugs is not associated with prolonged length of stay of hospitalized patients with Parkinson's disease - Skelly, Rob; Brown, Lisa; Fogarty, Andrew W. (Elsevier, 2017)
Background: Punctual delivery of dopaminergic medication to Parkinson's disease (PD) patients may be important in optimizing disease control. We tested the hypothesis that prompt delivery of l-dopa medications to emergency hospital inpatients was associated with a decreased length of stay in hospital.